Modeling and Analysis of Dynamic Systems - Esfandiari, Ramin S.; Lu, Bei. (Boca Raton: CRC Press, 2014)
"The goal of this second edition is essentially the same as that of the first edition, to provide the reader with a thorough knowledge of mathematical modeling and analysis of dynamic systems. Matlab, Simulink, and Simscape are introduced at the outset and are utilized throughout the book to perform symbolic, graphical, numerical, and simulation tasks. The textbook written at junior level, meticulously covers techniques for modeling dynamic systems, methods of response analysis, and in introduction to vibration and control systems. "--
Keywords: Mathematical models; Dynamics; System theory; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY & ENGINEERING / Nanotechnology & MEMS